Use of Nanoparticles in Completion Fluids as Dual Effect Treatments for Well Stimulation and Clay Swelling Damage Inhibition: An Assessment of the Effect of Nanoparticle Chemical Nature - Daniel López; Nicolas M. Chamat; Dahiana Galeano-Caro; Liliana Páramo; Diego Ramirez; David Jaramillo; Farid B. Cortés; Camilo A. Franco (Nanomaterials, 2023)
The objective of this study is to evaluate the role of nanoparticles with different chemical structures in completion fluids (CF) in providing a positive dual effect for well stimulation and clay swelling damage inhibition. Six types of commercial (C) or synthesized (S) nanoparticles have been incorporated into a commercial completion fluid. Doses varied between 100 and 500 mg·L−1. CF-nanoparticles were evaluated by fluid–fluid, fluid–nanoparticle, and fluid–rock interactions. The adsorption isotherms show different degrees of affinity, which impacts on the reduction of the interfacial tension between the CF and the reservoir fluids. Fluid–fluid interactions based on interfacial tension (IFT) measurements suggest that positively charged nanoparticles exhibit high IFT reductions. Based on contact angle measurements, fluid–rock interactions suggest that ZnO-S, SiO2-C, SiO2-S, and ZrO2 can adequately promote water–wet rock surfaces compared with other nanomaterials. According to the capillary number, ZnO-S and MgO-S have a higher capacity to reduce both interfacial and surface restrictions for crude oil production, suggesting that completion fluid with nanoparticles (NanoCF) can function as a stimulation agent. The clay swelling inhibition test in the presence of ZnO-S-CTAB and MgO-S-CTAB nanoparticles showed a 28.6% decrease in plastic viscosity (PV), indicating a reduction in clay swelling. The results indicate that a high-clay environment can meet the completion fluid’s requirements. They also indicate that the degree of clay swelling inhibition of the nanoparticles depends on their chemical nature and dosage. Finally, displacement tests revealed that CF with nanoparticles increased the oil linear displacement efficiency.